Word and Mystery: Hugo Mujica, María Rosa Lojo and Enrique Solinas’ Poetry of Ontological Search - Cárcano, Enzo (2020)
Between the XIXth and XXth centuries, German Romanticism, French Symbolism and Surrealism marked, in literature, the gradual substitution of the religious absolute with the poetic one. Poetry regained then an unknown importance, determined by its capacity to reach, through words, beyond the ordinary, the most unexplored and essential for human beings. In Argentina, many authors have poetically explored mystery as what escapes from the totalizing story built up by Modernity but, nevertheless, constitutes us. This article is an approach to the works of three of them, considered among the most original of these days: Hugo Mujica, María Rosa Lojo, and Enrique Solinas. With the aim of avoiding methodological or dogmatic encumbrances of concepts as “religious poetry”, the notion of “ontological search poetry”, which highlights the cognitive side of poetry against the commands of modern reasoning, is proposed.